An automated method for lumen and media-adventitia border detection in a sequence of IVUS frames. - Plissiti, M.E.
In this paper, we present a method for the automated detection of lumen and media-adventitia border in sequential intravascular ultrasound (IVUS) frames. The method is based on the use of deformable models. The energy function is appropriately modified and minimized using a Hopfield neural network. Proper modifications in the definition of the bias of the neurons have been introduced to incorporate image characteristics. A simulated annealing scheme is included to ensure convergence at a global minimum. The method overcomes distortions in the expected image pattern, due to the presence of calcium, employing a specialized structure of the neural network and boundary correction schemas which are based on a priori knowledge about the vessel geometry. The proposed method is evaluated using sequences of IVUS frames from 18 arterial segments, some of them indicating calcified regions. The obtained results demonstrate that our method is statistically accurate, reproducible, and capable to identify the regions of interest in sequences of IVUS frames.
Keywords: Ca; Hopfield neural network; Arterial segments; Boundary correction schemas; Calcified region; Calcium; Deformable models; Distortions; Energy function; Image pattern; Image segmentation; Intravascular ultrasound frames; Lumen automated detection; Media-adventitia border; Priori knowledge; Simulated annealing scheme; Vessel geometry